The first book of Moses, called Genesis [electronic resource]. - Peck, E. J. (Edward Jones), 1850-1924.; Bilby, J. (London : British and Foreign Bible Society, 1906)
In syllabic characters. Cover title: Eskimo Genesis. "Genesis in Eskimo, transcribed and changed from the Labrador dialect into that of Baffin's Land by the Rev. E.J. Peck assisted by Mr. J. Bilby."--t.p. verso. Electronic reproduction. Mode of access: Internet. 44